Analysis of the Relationship Between Islamic Spiritual Development and Work Motivation of Human Resources in Islamic Universities - Moch. Danu Kurniadi; Ilham Andrianto (UII Darullughah Waddawah Pasuruan, 2026)
Islamic spiritual development plays an important role in shaping the character and work ethic of human resources in Islamic educational institutions. STAI Ali bin Abi Thalib strives to balance intellectual and spiritual aspects through various spiritual development programs. However, further investigation is needed to determine the extent to which these programs influence the work motivation of staff and lecturers on campus. This study aims to describe the implementation of Islamic spiritual development for human resources and analyze the relationship between Islamic spiritual development and employee work motivation. The research method used is a correlational quantitative approach, with data collected through questionnaires and documentation. Data were analyzed using the Pearson Product Moment correlation test to determine the degree of relationship between the two variables. The results showed that: (1) Islamic spiritual development at STAI Ali bin Abi Thalib has been systematically implemented through various programs such as staff Islamic studies, Qur’an recitation and memorization, short lectures, and international seminars with Middle Eastern scholars. (2) The correlation test results show a value of r = 0.5246 > r_table = 0.2787 at the 5% significance level, indicating a positive and significant relationship between Islamic spiritual development and work motivation among human resources.